The Okinawa Trough and the Senkaku Islands sovereignty dispute in the East China Sea continental shelf delimitation - Nienaber, A.G. (Annelize Gertruida) (University of Pretoria, 2018)
Mini Dissertation (LLM)--University of Pretoria, 2018.